(3EYLGR GdJhGUd GdMVGQj GdEYdGej (B:s (3fMh hcGdI YQHjI OhdjI ddCfHGA (B/s - (3UYH, MSfs ((3dHfGf (B:s [(3Ohf fGTQ(B] (3,s, 1984)
(3aj gPG GdcJGH eSJMOKGJ GdGYdGejI GdJj GONdJ GdJMVQ GdGfSGfj aj WhQ GHOGYj LOjO jYQa GdGf HGdJWhQ GdMVGQj GdGYdGej h dgPG GdJWhhQ GjGJ JcfhdhLjI HUQjI h SeYjI h PGcQHI h OeGZjI QGFYI JJLdi aj GdJcfhdhLjG GdGYdGejI h dcf GdGge ef cd gPG GdGHOGY GdJcfhdhLj gh GdJhGUd GdGYdGej GddMXhj GdPj GfHKb efg h GdPj jJjM dGj GfSGf Gf HQi Gh jNGWH Gh jcGJH Gh jWGdY Gj GfSGf GNQ aj Gj dMXI GfGA Gddjd h GWQGa GdfgGQs
(3edGMXI (B: (3U(B.241-256s
Keywords: (3GdEYdGes; (3GdJhGUd GdEYdGejs